Will to Conquer! a Study of Media Representation of Female-Ministers in the 2014-2019 Jokowi-Kalla Cabinet - Triyono Lukmantoro (Jurnal Perempuan, 2014)
Media representations of women who have positions as ministers in President Joko Widodo’s Kabinet Kerja become phenomenon. On one side, media exposes aspects of successful side of female ministers. Media cited the statement of Presiden Jokowi that there are two “first woman” as appreciation. But, on the other side, media representations have masculinity character. For female minister who has “unique body performance”, the exposure of media are so excessive. Media had been trapped in the calculation of news values as reference for gathering news. The news values have been controlled by masculinity discourse that legitimate patriarchal regime of truth.